Effect of exacerbations on quality of life in patients with chronic obstructive pulmonary disease: a 2 year follow up study. Issue 5 (28th April 2004) - Miravitlles, M; Ferrer, M; Pont, À; Zalacain, R; Alvarez-Sala, J L; Masa, F; Verea, H; Murio, C; Ros, F; Vidal, R
Abstract : Background: A study was undertaken to evaluate exacerbations and their impact on the health related quality of life (HRQL) of patients with chronic obstructive pulmonary disease (COPD). Methods: A 2 year follow up study was performed in 336 patients with COPD of mean (SD) age 66 (8.2) years and mean (SD) forced expiratory volume in 1 second (FEV1 ) 33 (8)% predicted. Spirometric tests, questions regarding exacerbations of COPD, and HRQL measurements (St George's Respiratory Questionnaire (SGRQ) and SF-12 Health Survey) were conducted at 6 month intervals. Results: A total of 1015 exacerbations were recorded, and 103 (30.7%) patients required at least one hospital admission during the study. After adjustment for baseline characteristics and season of assessment, frequent exacerbations had a negative effect on HRQL in patients with moderate COPD (FEV1 35–50% predicted); the change in SGRQ total score of moderate patients with ⩾3 exacerbations was almost two points per year greater (worse) than those with <3 exacerbations during the follow up (p = 0.042). For patients with severe COPD (FEV1 <35% predicted) exacerbations had no effect on HRQL. The change in SGRQ total score of patients admitted to hospital was almost 2 points per year greater (worse) than patients not admitted, but this effect failed to show statistical significance in any severity group. There was a significant and independent seasonal effect on HRQL since SGRQ total scores were, on average, 3 points better in measurements performed in spring/summer than in those measured in the winter (p<0.001). Conclusions: Frequent exacerbations significantly impair HRQL of patients with moderate COPD. A significant and independent effect of seasonality was also observed.